Moralitas dan profesionalisme guru sebagai upaya meningkatkan mutu pendidikan - Tridara, Silvia Anugrah (Maliki Interdisciplinary Journal, 2024)
Teachers are valuable human resources who work to increase the quality of education, knowledge, attitudes, and abilities of professional educators. As a result, teacher competence should be consistently improved. Efforts have been made in a variety of disciplines to improve educational quality. Teachers play a significant role in implementing learning by acting as facilitators, motivators, and inspiring teachers to encourage students to achieve learning outcomes in accordance with educational goals. The purpose is to understand how the learning process, with the teacher as a key actor, may best improve the nature or competency of participants in order to fulfill national education goals. As a result, teachers must possess four competences in order to carry out their profession well. The first two competencies (pedagogical and professional competencies) relate to the task of educating and teaching, and the other two competencies (personality and social) relate to skills that are directly related to the spirit of teacher performance as individual and social beings. Teachers who maintain strong ethical principles serve as role models for their students. Simultaneously, the knowledge and skill displayed by teachers set the standards for educators as competent professionals. The professionalism of teachers is crucial in efforts to improve the quality of education and learning in schools. Thus, the commitment and competence of teachers as professional educators are essential requirements for achieving learning outcomes that meet national education standards.